Dysfunction of X-linked inhibitor of apoptosis protein (XIAP) triggers neuropathological processes via altered p53 activity in Huntington's disease. (September 2021) - Hyeon, Seung Jae; Park, Jinyoung; Yoo, Junsang; Kim, Su-Hyun; Hwang, Yu Jin; Kim, Seung-Chan; Liu, Tian; Shim, Hyun Soo; Kim, Yunha; Cho, Yakdol; Woo, Jiwan; Kim, Key-Sun; et al.
Graphical abstract: Highlights: This study found a new molecular mechanism that XIAP directly interacts with p53 and modulates p53 stability in medium spiny neuons. XIAP modulates the turnover of p53 via autophagy pathway. XIAP dysfunction leads to abnormal increase of p53 activity, mitochondrial dysfunction, and striatal neuron damage in HD. XIAP-p53 pathway can be a novel pathological marker and a therapeutic target in the pathogenesis of HD. Abstract: Mitochondrial dysfunction is associated with neuronal damage in Huntington's disease (HD), but the precise mechanism of mitochondria-dependent pathogenesis is not understood yet. Herein, we found that colocalization of XIAP and p53 was prominent in the cytosolic compartments of normal subjects but reduced in HD patients and HD transgenic animal models. Overexpression of mutant Huntingtin (mHTT) reduced XIAP levels and elevated mitochondrial localization of p53 in striatal cells in vitro and in vivo . Interestingly, XIAP interacted directly with the C-terminal domain of p53 and decreased its stability via autophagy. Overexpression of XIAP prevented mitochondrially targeted-p53 (Mito-p53)-induced mitochondrial oxidative stress and striatal cell death, whereas, knockdown of XIAP exacerbated Mito-p53-induced neuronal damage in vitro . In vivo transduction of AAV-shRNA XIAP in the dorsal striatum induced rapid onset of disease and reduced the lifespan of HD transgenic (N171-82Q) mice compared to WT littermate mice. XIAP dysfunction led to ultrastructural changes of the mitochondrial cristae and nucleus morphology in striatal cells. Knockdown of XIAP exacerbated neuropathology and motor dysfunctions in N171-82Q mice. In contrast, XIAP overexpression improved neuropathology and motor behaviors in both AAV-mHTT-transduced mice and N171-82Q mice. Our data provides a molecular and pathological mechanism that deregulation of XIAP triggers mitochondria dysfunction and other neuropathological processes via the neurotoxic effect of p53 in HD. Together, the XIAP-p53 pathway is a novel pathological marker and can be a therapeutic target for improving the symptoms in HD.